What Drives Green Choices? A Systematic Literature Review of Consumer Behavior and Sustainability - Luki Sri Anggorowati; Ihwan Susila; Kussudyarsana Kussudyarsana; Arumugam G. Sithamparam (Relevance: Journal of Management and Business, 2026)
The shift towards sustainable consumption patterns is becoming more urgent as awareness of environmental impacts increases. However, consumer adoption of green products still faces various barriers. This study aims to identify variables, theories, and methodologies that influence consumer behavior towards green products through a systematic literature review (SLR) of 89 scientific articles selected using the PRISMA protocol. The results show that psychological variables such as environmental concern and perceived consumer effectiveness are the main drivers of pro-environmental behavior. In addition, there is also the influence of social norms, cultural values, perceived price, and product accessibility. Theoretically, the Theory of Planned Behavior (TPB) is the most widely used approach, followed by Value-Belief-Norm (VBN) and other multidimensional models. In terms of methodology, quantitative approaches such as Structural Equation Modeling (SEM) are increasingly complemented by mixed methods and contextual analysis. The findings emphasize the importance of a holistic approach in policy development and marketing strategies to increase the adoption of green products.